EFFECTIVENESS OF WILLIAM FLEXION EXERCISE TO REDUCE PAIN INTENSITY ON LOW BACK PAIN (LBP) OF WOODCARVERS IN BALI, INDONESIA - A.A Istri Dalem Hana Yundari; Putu Puspita Wulandari Mas (Proceedings of the International Conference on Applied Science and Health, 2018)
Background: Previous study shown 8 of 10 woodcarver in Bali experience low back pain (LBP), a clinical syndrome with major symptoms of pain or discomfort sense in the lower back area. A William’s flexion exercise, an exercise program consisting of six kinds of movements, may decrease the pain by decreasing the lumbar lordosis (flexion). This study is to evaluate the effect of William’s Flexion Exercise in reducing pain intensity of LBP to woodcarvers in Bali, Indonesia. Methods: This study employed a quasi-experimental design with pretest-posttest approach and control group. Out of 42 woodcarvers in Mas Village, Gianyar, Bali, Indonesia, 20 sculptors were selected by a purposive sampling technique, and then were distributed equally to control and treatment group. Treatment group was given William’s Flexion Exercise 2 times every week for 4 weeks. Pain intensity was measured by pain scale; low pain (scale 1-3), moderate (4-6), and high pain (7-10). Wilcoxon and Mann Whitney test were used for statistical analysis. Results: The study found that William’s Flexion Exercise given to the woodcarvers significantly reduce the pain intensity (p value = 0.000). Conclusions: William’s flexion exercise is recommended to be given to the woodcarver to reduce low back pain.